Sequential Antibiotic Therapy: Effective Cost Management and Patient Care - Lionel A Mandell; Michel G Bergeron; Marie J Gribble; Peter J Jewesson; Donald E Low; Thomas J Marrie; Lindsay E Nicolle (Canadian Journal of Infectious Diseases)
The escalating costs associated with antimicrobial chemotherapy have become of increasing concern to physicians, pharmacists and patients alike. A number of strategies have been developed to address this problem. This article focuses specifically on sequential antibiotic therapy (sat), which is the strategy of converting patients from intravenous to oral medication regardless of whether the same or a different class of drug is used. Advantages of sat include economic benefits, patient benefits and benefits to the health care provider. Potential disadvantages are cost to the consumer and the risk of therapeutic failure. A critical review of the published literature shows that evidence from randomized controlled trials supports the role of sat. However, it is also clear that further studies are necessary to determine the optimal time for intravenous to oral changeover and to identify the variables that may interfere with the use of oral drugs. Procedures necessary for the implementation of a sat program in the hospital setting are also discussed.